2020
DOI: 10.21448/ijsm.660578
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Flavonoid Contents and Evaluation of in vitro Antioxidant Activities of the Extract of Selected Citrus Fruit Peel

Abstract: Flavonoids capture and neutralize the oxidative agents, and quench free radicals. The peel which represents almost one half of the fruit mass has been found to be the main sources of total phenols and flavonoids in the citrus fruit. In present study, flavonoid content and in vitro antioxidant activities of ethanol extracts from some selected citrus fruit peels grown in Ethiopia were determined. Colorimetric aluminum chloride was used for flavonoid content determination. In vitro antioxidant properties of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…According to the same report, there was no correlation between both total phenolic and flavonoid content against radical scavenging activity in linear regression analysis. On the contrary, several reports showed a strong correlation on phenolic and flavonoid contents of citrus fruit peel extracts against DPPH assay 22,23 . In general, the fruit's peel contains a higher concentration of antioxidant substances than the fruit's flesh 24 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…According to the same report, there was no correlation between both total phenolic and flavonoid content against radical scavenging activity in linear regression analysis. On the contrary, several reports showed a strong correlation on phenolic and flavonoid contents of citrus fruit peel extracts against DPPH assay 22,23 . In general, the fruit's peel contains a higher concentration of antioxidant substances than the fruit's flesh 24 .…”
Section: Discussionmentioning
confidence: 88%
“…A qualitative phytochemical screening test showed significant indication of certain metabolites' presence 26 . Many scientific articles stated that phytochemical content and composition varies due to different factors and one of the factors indicated is environmental difference and variety of the plant 22 . The presence of phytochemical such as alkaloid, flavonoid, phenol, tannin and terpenoid in richantioxidant liang tea.…”
Section: Discussionmentioning
confidence: 99%
“…C. aurantium, C. limetta and C. limon. Erba et al [37] reported the peel of orange, mandarin, lime and lemon has the highest DPPH scavenging activity but different result of DPPH radical scavenging activity was also reported by Singh & Immanuel [38].…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 83%
“…The above findings agreed with [ 44 ]. According to the correlation analysis performed by [ 46 ], the essential factor in determining the antioxidant activity potency of phenolic and flavonoids is their molecular structure rather than their content. Therefore, the total contents of phenolic and flavonoids cannot be a critical factor in predicting antioxidant efficiency.…”
Section: Resultsmentioning
confidence: 99%